Breaking Barriers: Empowering Women’s Decision-Making in Nepal’s Development Programs - Limbu, Lila Prasad; Shrestha, Purnima (Tribhuvan University Journal, 2023)
This research paper investigates women’s role and participation in decision-making in development committees in Nepal and their representation in different development committees and situation of their participation. The study found that females are more likely to be involved in development committees than males. However, their representation of leadership positions is still low due to social and cultural barriers. Female views are not always considered equally in meetings due to their lower position in committees and gender. So, this paper highlights the need for gender, caste, and class-sensitive policies and programs that promote women’s active participation in development program’s decision-making process and address socio-cultural barriers to women’s role in leadership in their communities.